2017
DOI: 10.5489/cuaj.4541
|View full text |Cite
|
Sign up to set email alerts
|

Publicly funded overactive bladder drug treatment patterns in Ontario over 15 years: An ecological study

Abstract: Introduction: Medication is an important option for patients with overactive bladder (OAB), with four different drugs approved over the last 10 years including the first non-anticholinergic treatment, mirabegron. We set out to describe the number and rate of users of medication for the management of OAB over the last 15 years among residents of Ontario, Canada covered by the public drug programs. Methods: We conducted a population-based, repeated cross-sectional study examining quarterly publically-funded pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The β3-adrenergic agonist mirabegron was introduced into the treatment of iOAB in 2012. Its safety and efficacy in the treatment of this condition have been confirmed in a large number of well-designed studies [12]. In this study we also found improvement in the mean volume of per catheterization.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The β3-adrenergic agonist mirabegron was introduced into the treatment of iOAB in 2012. Its safety and efficacy in the treatment of this condition have been confirmed in a large number of well-designed studies [12]. In this study we also found improvement in the mean volume of per catheterization.…”
Section: Discussionsupporting
confidence: 80%
“…Clinical trials have demonstrated its efficacy and safety [9] [10] and observational studies suggest improved persistence and adherence when compared to antimuscarinics [11]. As such, it has become a commonly used overactive bladder medication in the general population [12]. But few studies were carried on the treatment of mirabegron for NDO.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have demonstrated its efficacy and safety, and observational studies suggest improved persistence and adherence when compared to antimuscarinics . As such, it has become a commonly used overactive bladder medication in the general population . There is interest in using mirabegron for patients with NLUTD due to the potentially better safety and tolerability profile; however, there is limited evidence of its efficacy in this population .…”
Section: Introductionmentioning
confidence: 99%
“…7 As such, it has become a commonly used overactive bladder medication in the general population. 8 There is interest in using mirabegron for patients with NLUTD due to the potentially better safety and tolerability profile 5,9 ; however, there is limited evidence of its efficacy in this population. 10,11 There are potentially serious consequences of inadequately treated neurogenic bladder parameters; one study found that almost 20% of SCI patients required surgical invention for adverse urodynamic parameters over a 5-year period.…”
mentioning
confidence: 99%
“…This set in motion an important new therapeutic option for patients with overactive bladder (OAB). Once available for use, mirabegron rapidly became one of the most commonly used oral therapies for OAB (2,3).…”
mentioning
confidence: 99%